Association of Soluble HLA-G Plasma Level and HLA-G Genetic Polymorphism With Pregnancy Outcome of Patients Undergoing in vitro Fertilization Embryo Transfer - Nowak, Izabela; Wilczyńska, Karolina; Radwan, Paweł; Wiśniewski, Andrzej; Krasiński, Rafał; Radwan, Michał; Wilczyński, Jacek R.; Malinowski, Andrzej; Kuśnierczyk, Piotr (Frontiers in Immunology, 2020)
Infertility is currently a growing problem observed around the world and is estimated to affect between 8 and 12% of reproductive-aged couples worldwide. Artificial reproductive techniques are the last chance for couples seeking their own child. Human leukocyte antigen (HLA)-G expression has been suggested as an immunomodulatory molecule influencing pregnancy outcome. The HLA-G gene encodes either membrane-bound or/and soluble proteins. The aim of this study was the evaluation of soluble HLA-G (sHLA-G) role and its gene polymorphism in success of implantation after in vitro fertilization embryo transfers (IVF-ETs) in different clinical protocols. We tested HLA-G polymorphism in 3 positions: rs1632947: c-964G>A; rs1233334: c.-725G>C/T in promoter region; rs371194629: c.*65_*66insATTTGTTCATGCCT in 3’UTR of exon 8, in 389 patients who underwent IVF-ETs and 320 women with healthy born children after natural conception. Among the patient group, 239 women were with recurrent implantation failure and 117 women had an ongoing pregnancy or a child born after IVF-ET. We found certain rs1632947-rs1233334-rs371194629 HLA-G haplotypes and diplotypes were associated with infertility, while others were protective. The lowest secretors of sHLA-G were G-C-ins haplotype carriers (37.21 IU/mL), while the highest - G-C-del carriers (73.80 IU/mL). Other haplotype carriers were intermediate secretors. In our study, regardless of possessed haplotype by the patient, 59.73 IU/mL sHLA-G was threshold value with the best sensitivity (58.82%) and specificity (66.10%) to discriminate patients who achieved and maintained pregnancy from those who did not conceive or they had miscarriage (p = 0.0085, likelihood ratio 1.74, 95% CI = 0.55-0.78). However, we do not exclude that factors other than sHLA-G may also contribute to complications in pregnancy. In addition, we found that IVF patients in cycles when frozen/thawed embryo was transferred secreted higher soluble HLA-G levels than patients with fresh embryo transferred (p = 0.021). Moreover, correlation analysis of sHLA-G concentration measured before and after embryo transfer for particular patients indicated short ovarian stimulation with gonadotropin-releasing hormone (GnRH) antagonist as more beneficial than long protocol with GnRH agonist. Our study confirm a role of HLA-G polymorphism in infertility and soluble HLA-G in the early stages of pregnancy.